Treatment of central serous chorioretinopathy with topical NSAIDs - Bahadorani S (Dove Medical Press, 2019)
Sepehr Bahadorani,1 Kyle Maclean,1 Kendall Wannamaker,1 Edward Rickie Chu,1 Nathan Gresores,2 Jeong-Hyeon Sohn,1 Roberto Diaz-Rohena,1 Michael A Singer21Department of Ophthalmology, University of Texas Health Science Center at San Antonio, San Antonio, TX, USA; 2Medical Center Ophthalmology Associates, San Antonio, TX, USAPurpose: Central serous chorioretinopathy (CSCR) is a common retinopathy that is often observed until resolution. The purpose of this study is to evaluate the effects of topical nonsteroidal anti-inflammatory drugs (NSAIDs) on timing of CSCR recovery.Methods: An IRB-approved retrospective review was conducted on patients that had been diagnosed with a new-onset, symptomatic case of CSCR. Patients were either observed only (13 untreated eyes) or treated with topical bromfenac or nepafenac (14 eyes) over an average of about a 4–5 week follow-up period.Results: There was no statistical significance between central macular thickness (CMT) and visual acuity of treatment and control groups at the initial presentation. However, at the follow-up visit, CMT reductions in the treatment group were significantly higher than in the control group (p<0.006).Conclusion: Use of topical NSAIDs in the treatment of acute CSCR leads to a faster rate of reduction in the subretinal fluid volume over a follow-up period of a few weeks.Keywords: central serous chorioretinopathy, CSCR, CSC, NSAIDs, bromfenac, nepafenac, subretinal fluid, SRF